Moral responsibility of man as khalifah: an exposition of the foundations of a just order - Sulaiman, Kabuye Uthman (Zes Rokman Resources, 2016)
The question of morality is one of the major themes of the Qur’an and Sunnah, and a topic of concern for philosophers and psychologists for thousands of years. It is the reason for creating man as khalifah (vicegerent) and the descent of divine guidance to mankind. This paper discusses the moral responsibility of man as khalifah as enshrined in the Qur’an and Sunnah, and focuses largely upon the requirements of a just order. The paper begins with a brief introduction on the importance of moral responsibility. It concludes with a summary of man’s moral responsibility in Islam and the foundations of a just order. Using the insights from the Qur’an and Sunnah and quotations from some scholarly articles and books, the paper contends that: firstly, moral refinement is one of the objectives of salat, zakat, sawm and hajj and therefore the greatest challenge to every individual Muslim; secondly, moral responsibility is the greatest challenger to modern science and civilization; and thirdly, the decline of moral values is one of the factors that promote the decline and fall of civilizations. Finally, the paper contrasts al-Tawhid (the oneness of Allah) to positivism, utilitarianism and libertarianism as foundations of morality.